Initiation of Pos Gizi as a Community-Based Stunting Prevention - Wiralis Wiralis; Imanuddin Imanuddin; Hariani Hariani; Teguh Faturrahman; Suwarni Suwarni (CV Media Inti Teknologi, 2024)
This community service activity is aimed at the initiation of Pos Gizi a community-based in Bajo Indah village. The method of this community service activity uses the training for Pos Gizi cadres for 3 days. The criteria for the Pos Gizi 10 cadres are: being able to read and write, availability of time, domicile, interest and motivation, and community trust. The instruments used were questionnaires and observation sheets. The cadre training stages are the preparation, implementation, and evaluation stages. Data was analyzed descriptively and statistic paired t-test. The result of community services is a nutrition post institution was formed based on the decree of the Bajo Indah village head. The Bajo Indah village Pos Gizi has a place of activity determined by the village head, namely the village office building, with meeting room facilities, a nutrition consultation room, and a mini kitchen. Each room is equipped with facilities such as tables, chairs, document cabinets, weighing equipment, microtonal, and LILa tape, the mini kitchen is equipped with cooking equipment in the form of a gas stove, pan, basin, plate, spoon, glass, cutting board, knife, frying pan, and cooking pot. Pos Gizi cadre training significantly increased the knowledge and skills of cadres p <0.05 (sig.0.000). So, it can be concluded that the community service activities have formed a Pos Gizi institution and increased the knowledge and skills of cadres to carry out their duties as Bajo Indah village Pos Gizi cadres.